Konflik Batin pada Novel Percobaan Setia Karya Soeman H.S. dalam Dimensi Budaya Melayu: Analisis Hierarki Kebutuhan Maslow - Aditia, Sidiq; Maharani Umaya, Nazla (GERAM, 2024)
This study examines the inner conflicts in the novel Percobaan Setia by Soeman H.S. using Abraham Maslow's hierarchy of needs theory. The novel portrays the struggles of Syamsuddin, an orphan, as he faces psychological challenges, social pressures, and economic constraints that trigger inner conflicts.  The findings reveal that the need for love and belonging (17 conflicts) and esteem (15 conflicts) are the dominant sources of conflict, whereas physiological needs account for only 9 conflicts. These results highlight that unmet emotional and social needs more frequently drive inner conflicts compared to physical needs. The resolution of these conflicts underscores the importance of emotional relationships in achieving psychological balance. This research contributes to theoretical development by linking the hierarchy of human needs to literary narratives, particularly within the context of Malay culture. Practically, the findings can be utilized in literature teaching to deepen character analysis and in bibliotherapy to explore emotional experiences through literary characters.